Mapping of a hybrid insulin peptide in the inflamed islet β-cells from NOD mice - Wenzlau, Janet M.; Peterson, Orion J.; Vomund, Anthony N.; DiLisio, James E.; Hohenstein, Anita; Haskins, Kathryn; Wan, Xiaoxiao (Frontiers in Immunology, 2024)
There is accumulating evidence that pathogenic T cells in T1D recognize epitopes formed by post-translational modifications of β-cell antigens, including hybrid insulin peptides (HIPs). The ligands for several CD4 T cell clones derived from the NOD mouse are HIPs comprised of a fragment of proinsulin joined to peptides from endogenous β-cell granule proteins. The diabetogenic T cell clone BDC-6.9 reacts to a fragment of C-peptide fused to a cleavage product of pro-islet amyloid polypeptide (6.9HIP). In this study we used a monoclonal antibody (MAb) to the 6.9HIP to determine when and where HIP antigens are present in NOD islets during disease progression and with which immune cells they associate. Immunogold labeling of the 6.9HIP MAb and organelle-specific markers for electron microscopy were employed to map the subcellular compartment(s) in which the HIP is localized within βcells. While the insulin B9-23 peptide was present in nearly all islets, the 6.9HIP MAb stained infiltrated islets only in NOD mice at advanced stages of T1D development. Islets co-stained with the 6.9HIP MAb and antibodies to mark insulin, macrophages and dendritic cells indicate that 6.9HIP co-localizes within insulin-positive β-cells as well as intra-islet APCs. In electron micrographs, the 6.9HIP co-localized with granule structures containing insulin alone or both insulin and LAMP1 within β-cells. Exposing NOD islets to the ER stress inducer tunicamycin significantly increased levels of 6.9HIP in subcellular fractions containing crinosomes and dense-core granules DCGs. This work demonstrates that the 6.9HIP can be visualized in the infiltrated islets and suggests that intra-islet APCs may acquire and present HIP antigens within islets.